2018
DOI: 10.3122/jabfm.2018.01.170288
|View full text |Cite
|
Sign up to set email alerts
|

Is It Idiopathic Pulmonary Fibrosis or Not?

Abstract: Pulmonary fibrosis is not uncommon. Usual interstitial pneumonitis (UIP)/idiopathic pulmonary fibrosis (IPF) is the most common of the idiopathic pulmonary fibrotic diseases and has the worst prognosis with a mean life expectancy of 3.8 years. The American Thoracic Society has provided guidelines for the accurate diagnosis of IPF.In 2014

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 27 publications
(37 reference statements)
0
23
0
Order By: Relevance
“…A 10-year mortality rate of 16% has been reported in patients with lung fibrosis [106], which, allowing for comorbidities and other causes of death, may suggest that a small subset of patients have the progressive-fibrosing phenotype despite appropriate therapy. Acute exacerbations have not been reported in stage IV pulmonary sarcoidosis [105].…”
Section: Sarcoidosismentioning
confidence: 90%
See 2 more Smart Citations
“…A 10-year mortality rate of 16% has been reported in patients with lung fibrosis [106], which, allowing for comorbidities and other causes of death, may suggest that a small subset of patients have the progressive-fibrosing phenotype despite appropriate therapy. Acute exacerbations have not been reported in stage IV pulmonary sarcoidosis [105].…”
Section: Sarcoidosismentioning
confidence: 90%
“…Extensive parenchymal destruction and mycetoma are also occasionally observed. A UIP pattern of lung injury is uncommonly seen in patients with fibrosing pulmonary sarcoidosis, although honeycombing may be seen in the upper zones of the lungs [105].…”
Section: Sarcoidosismentioning
confidence: 99%
See 1 more Smart Citation
“…Accurate diagnosis requires a multidisciplinary approach with incorporation of clinical, pathophysiological, immunological and imaging information. This comprehensive testing contributes to the cost of healthcare [15][16][17][18][19][20]. It has been reported that up to 34% of ILD patients do not receive a final diagnosis for ⩾2 years during which time we anecdotally observe repetition of diagnostic tests and consultations.…”
Section: Diagnosis and Prognosismentioning
confidence: 99%
“…16 From the family physician perspective, the original diagnosis is often the quandary-when is it pulmonary fibrosis with its poor prognosis, and when is it something else that is more currently treatable, and which treatment should be used? Salvatore et al 16 provide a helpful review of current diagnosis and treatment. A reader also provides us a letter about the importance of being an ABFM diplomate.…”
Section: Othermentioning
confidence: 99%